Pengaruh Penggunaan Stratei Pembelajaran dengan Peta Konsep Terhadap Penguasaan Pengetahuan Faktual dan Konseptual dalam Materi Siklus Air pada Siswa Kelas V - Bambang Edi Purnomo; Irwan Koto; Agus Susanta (UNIB Press, 2024)
Efforts that can be made to improve the quality and learning outcomes of elementary school students include using appropriate learning strategies. One of them is a learning strategy with concept maps. This study aims to determine the effect of using learning strategies with concept maps on the mastery of factual and conceptual knowledge in the Water Cycle material for fifth grade students. This research is a quantitative study. The method used is the experimental method, with a quasi-experimental design research type. The instruments provided consisted of 10 factual knowledge dimensions and 10 conceptual questions. Data collection techniques were carried out using test and non-test techniques. Data analysis techniques consist of quantitative data analysis and qualitative data analysis. The results showed that there was a difference in the increase in factual knowledge mastery between the experimental and control classes by 22.14% and conceptual knowledge by 17.78%. It can be concluded that a) There is a significant effect (a = 5%) using learning strategies with concept maps on the mastery of factual knowledge. b) There is a significant effect (a = 5%) using learning strategies with concept maps on the mastery of conceptual knowledge. c) There is no significant difference between the mastery of factual and conceptual knowledge through the use of learning strategies with concept maps in the Water Cycle material for fifth grade students.